The Effect of Tourism Attraction and Destination Image on Tourist Motivation Bandung During COVID-19 Recovery - Puspa Savira; Rikantini Widiyanti; Any Ariani Noor (Journal of Tourism Sustainability, 2022)
For years Bandung could attract some tourists to visit. However, Covid-19 has crushed the tourism sector in the world, including Bandung City. Covid-19 changes behavior and visit intention to destination. According to a new situation, this research examines tourism motivation in visiting Bandung City through the influence of tourist attraction and destination image. This research was conducted in quantitative analysis, which collected data by distributing questionnaires to 114 respondents from random sampling. The sampling technique used was quota sampling where the number of the population was unknown and also the sample selection was not chosen at random but there were defined characteristics, namely that they were domestic tourists who had traveled to Bandung City. The analysis of this research uses Multiple Linear Regression. The results of this study can see tourist attractions that can attract foreign tourists, know the image of destinations from the city of Bandung, and prove that the variables of tourist attraction and image of destinations do not really affect the motivation of tourists who come to the city of Bandung.